Perspectives on Analytical Treatment Interruptions in People Living with HIV and Their Health Care Providers in the Landscape of HIV Cure-Focused Studies - Lau, Jillian S Y; Smith, Miranda Z; Allan, Brent; Martinez, Cipriano; Power, Jennifer; Lewin, Sharon R; McMahon, James H (AIDS research and human retroviruses, 2020)
Analytical treatment interruptions (ATIs) aim to assess effects of HIV cure-focused interventions, but poses potential risks. Understanding of ATI acceptability among people living with HIV (PLHIV) and their HIV health care providers (HHP) is limited. Two international online surveys for PLHIV and HHP assessed understanding and acceptability of monitoring strategies during ATI. Survey items included the following: frequency of CD4, viral load (VL) and clinical assessment, CD4 and VL threshold to restart antiretroviral therapy (ART), acceptability of detectable viremia during ATI, and potential risks of ATI. Responses were collected from July 2017 to January 2018, and a descriptive analysis was performed. Responses to questions asked in both surveys were compared by χ test. Four hundred forty-two completed the PLHIV survey: 22% identified as female, 39% older than 50 years of age, and 64% identified as gay/homosexual/lesbian. Ninety-five percent were on ART, of which 83% reported an undetectable VL. The preferred frequency of CD4, VL, and clinical monitoring during ATI was monthly. Thirty-five percent of respondents preferred VL to remain undetectable during ATI and would not accept any sustained period of viremia, compared to 18% of 144 HHP ( < .01). Having previously interrupted ART predicted preference for VL to remain undetectable during ATI (odds ratio 0.6, = .05). Both clinicians and PLHIV were concerned about HIV transmission during ATI. Our work demonstrates that PLHIV expectations of ATI in cure-focused clinical trials do not align with current practices, with PLHIV less accepting of viremia during ATI and preferring less frequent monitoring. Clear education messages and careful consent processes need to be developed in relationship to ATIs in HIV cure research.